The Identification of Two RNA Modification Patterns and Tumor Microenvironment Infiltration Characterization of Lung Adenocarcinoma - He, Wan; Lin, Gengpeng; Pan, Chaohu; Li, Wenwen; Shen, Jing; Liu, Yangli; Li, Hui; Wu, Dongfang; Lin, Xuejia (Frontiers in Genetics, 2022)
Background: RNA modification plays an important role in many diseases. A comprehensive study of tumor microenvironment (TME) characteristics mediated by RNA modification regulators will improve the understanding of TME immune regulation. Methods: We selected 26 RNA modification "writers" of lung adenocarcinoma (LUAD) samples and performed unsupervised clustering analysis to explore RNA modification pattern in LUAD. Differentially expressed genes (DEGs) with RNA modification patterns were screened to develop a “writers” of RNA modification score (WM score) system. The infiltration ratio of TME cell subsets was analyzed by CIBERSORT. Results: We identified two RNA modification modes showing different characteristics of overall survival (OS) and TME cell infiltration. According to WM score, LUAD patients were divided into high-WM score group and low-WM score group. High-scored patients had poor prognosis and higher tumor mutation burden (TMB), they were more sensitive to four LUAD therapies (Erlotinib, XA V939, Gefitinib, and KU-55933) and more clinically responsive to PD-L1 treatment. Those with low WM score showed higher sromal score, ESTIMATE score and survival chance. Conclusions: Our work revealed the potential role of RNA modification patterns in TME, genetic variation, targeted inhibitor therapy and immunotherapy. Identifying RNA modification pattern of LUAD patients help understand the characteristics of TME and may promote the development of immunotherapy strategies.